Penerapan Hypnosis Lima Jari pada Penderita Hipertensi di Kelurahan Legok Kota Jambi - Putri, Vevi Suryenti; M, Rino; Pebrianti, Dwi Kartika (Universitas Baiturrahim, 2024)
Non-Communicable Diseases (PTM) are the leading cause of death globally. One of the Non-Communicable Diseases (PTM) which is the most serious health problem today is hypertension. Factors that influence the occurrence of hypertension are both risk factors that cannot be changed, such as age, heredity, and risk factors that can be changed, namely consumption of salt, cholesterol, caffeine and alcohol, obesity, lack of exercise, stress and unstable emotional conditions such as anxiety. Management of anxiety nursing in hypertensive patients by administering five finger hypnosis therapy. The choice of giving five finger hypnotic therapy is because in general people with hypertension have problems with their thoughts, so if anxiety is not treated it will cause anxiety which can aggravate the patient's condition. The goal in providing community service is to increase respondents' knowledge about hypertension and the management of hypertension with five finger hypnosis. The method of providing community service is by conducting lectures, discussions, question and answer and demonstrations about hypertension and nursing management with five finger hypnosis. The method of measuring devotion was carried out pre-test and post-test of the respondent's knowledge about hypertension and the management of the five-finger hypnosis method. Respondents in this activity were hypertension sufferers in the Legok Village, RT 39, Jambi City, aged 45-60 years. The number of participants in the activity was 20 participants. The results of the activities carried out during the 1 week of the activity showed an increase in participants' knowledge about hypertension by 48%, and respondents were able to do five finger hypnosis by 52%.It can be concluded that there was an increase in participants' knowledge after carrying out the activity.